SINYAL KUALITAS LABA DARI KEBIJAKAN DIVIDEN PADA ASEAN ASSET CLASS PUBLICLY LISTED COMPANIES - Theresia Siwi Kartikawati; Endang Kusmana; Zulham AlFarizi; Qisty Ardhi; Utin Nina Hermina (Bajang Institute, 2023)
This research has aims to prove the effect of dividend payments on the quality of the company's earnings and it’s impact on the predictability of the company's cash flows in the future future empirically. Population in research these are some companies in the region ASEAN which is included in the list of ASEAN Asset Class Publicly Listed Companies. Research methods use the associative method to see the relationship between the existing variables. Results of This research will show that the company who have paid dividends consistently proven will have better earnings quality than companies that do not pay dividends to company shareholders. As well company size can affect the quality the company's profit shows that the amount of coefficient of firm size is positive and significant to the two proxies of earnings quality used in research, namely ADA and AAQ. So it can be concluded that the size larger companies will present higher earnings quality. While results testing of other variables shows company growth and sales growth the company has no significant effect on the quality of earnings owned by a company.